Strengthening Interfaith Relations: (Some Toughts on Humility Strategies) - Siti Syamsiatun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The conversation regarding the above title by confessing my deep wonder about human’s continuing, never ending endeavor to grapple, to make sense, to find significance, to understand about faith and religion. For ages, since time of immemorial till today, we-humans, endlessly experience, and struggle to understand and to theorize special phenomena of important behaviors in response to significant questions of our lives: why we are here, where we come from, what are the purposes of our existence, why we cease to live, what happens after this, etcetera. These complex important phenomena come to be known widely in our todays’ world as faith or religion. The understanding and experiences on faith and religion, mine and others, are changing overtime, thus my talking points in this document are not my final narratives on the issues of interfaith relations. Hopefully such changes in experiences and understanding lead me to become a better human person, a better member of community, a better global citizen. All the data I use in this short paper is collected and derived from observation and documentation study. Having said these, I sincerely invite feedbacks and input from colleagues participating in this important academic event.